Impact on clinical outcomes from transcatheter closure of the Fontan fenestration: A systematic review and meta-analysis - Greenleaf, Christopher E.; Lim, Zhia Ning; Li, Wen; LaPar, Damien J.; Salazar, Jorge D.; Corno, Antonio F. (Frontiers in Pediatrics, 2022)
Background Meta-analysis of the impact on clinical outcome from transcatheter closure of Fontan fenestration. Methods Cochrane, Embase, MEDLINE, and Open-Gray were searched. Parameters such as changes in oxygen saturation, cavo-pulmonary pressure, maximum heart rate during exercise, exercise duration, and oxygen saturation after fenestration closure were pooled and statistical analysis performed. Results Among 922 publications, 12 retrospective observational studies were included. The included studies involved 610 patients, of which 552 patients (90.5%) had a fenestration. Of those patients, 505 patients (91.5%) underwent attempt at trans-catheter closure. When it could be estimated, the pooled overall mean age at trans-catheter fenestration closure was 6.6 ± 7.4 years, and the mean follow-up time was 34.4 ± 10.7 months. There were 32 minor (6.3%) and 20 major (4.0%) complications during or after trans-catheter Fontan fenestration closure. The forest plots demonstrate that following fenestration closure, there was a significant increase in the mean arterial oxygen saturation of 7.9% (95% CI 6.4–9.4%, p < 0.01). There was also a significant increase in the mean cavo-pulmonary pressure of 1.4 mmHg (95% CI 1.0–1.8 mmHg, p < 0.01) following fenestration closure. The exercise parameters reported in 3 studies also favored closing the fenestration as well, yet the exercise duration increase of 1.7 min (95% CI 0.7–2.8 min, p < 0.01) after fenestration closure is probably clinically insignificant. Conclusion Late closure of a Fontan fenestration has the impact of improving resting oxygen saturation, exercise oxygen saturation, and a modest improvement of exercise duration. These clinical benefits, however, may be at the expense of tolerating slightly higher cavo-pulmonary mean pressures.